Pairwise Lower Separation Axioms in C ̌ech Fuzzy Soft Bi-Closure Spaces - Mohamad Thijeel Hamood; R. N. Majeed (Al-Qadisiyah Journal of Pure Science, 2021)
The idea of ech fuzzy soft bi-closure space (  bicsp)  is a new one, and its basic features are defined and studied in [1]. In this paper, separation axioms, namely pairwise, , pairwise semi-(respectively, pairwise pseudo and pairwise Uryshon) - fs bicsp's are introduced and studied in both ech fuzzy soft bi-closure space and their induced fuzzy soft bitopological spaces. It is shown that hereditary property is satisfied for ,  with respect to ech fuzzy soft bi-closure space but for other mentioned types of separations axioms, hereditary property satisfies for closed subspaces of ech fuzzy soft bi-closure space.